Energy Storing Plant Stem with Cytocompatibility for Supercapacitor Electrode. (23rd September 2021) - Liang, Jieying; Yu, Mengying; Liu, Jian; Yu, Zhichun; Liang, Kang; Wang, Da‐Wei
Abstract: Endowing natural biological objects, such as plants or their parts, with non‐native and targeted electroactivity is an appealing challenge in nano‐biotechnology, which if addressed will circumvent the biomass carbonization and promote the emission‐free transformation of raw bioresources for green energy. Here, a general concept to produce supercapacitor electrodes from plant stems is reported, which exhibit promising electroactivity and cytocompatibility. The core innovation is to apply a conformal electroactive coating onto the surfaces of hyperbranched channels of plant stem by interfacial self‐assembly. The electroactive plant stem can be employed as a functional supercapacitor electrode, the capacitance of which is up to 2.35 F. Furthermore, more than 98% cell viability is well maintained after the plant stem electrode is incubated with MCF‐7 cells for 72 h, and even after 100 discharge–recharge cycles, suggesting this plant stem electrode has excellent cytocompatibility and cycling stability. This energy storing plant stem gives rise to new opportunities for integrating natural bioresources with artificial electroactive nanomaterials for cytocompatible energy storage devices. Abstract : A novel energy storing plant stem and its usability as a supercapacitor electrode is reported. The plant stem directs the interfacial assembly of a conformal polyaniline coating that renders electroactivity to the plant stem, which can be employed as a functional supercapacitor electrode. Furthermore, this plant electrode demonstrates excellent cytocompatibility and cycling stability.